The Epidemiology and Control Myiasis in Indonesia - S Partoutomo (Indonesian Center for Animal Research and Development, 2000)
Myiasis caused by screwworm of Chrysomya bezziana fly has been widely distributed in Indoenesia for years, however myiasis as a disease problem is only reported in local cattle raised under semiextensive management system in West Nusa Tenggara, East Nusa Tenggara, South and North Sulawesi. In local cattle raised under an intensive management system in Java, Madura and Bali, disease problems caused by myiasis are unknown. Australian Brahman and Brahman cross cattle which were raised under a ranch system in South Sulawesi and East Sumba, and Merino sheep raised under intensive management system in Bogor and Jakarta are more susceptible to myiasis than local animals. Traditional medicines including tobacco extract, petrol and bettery acid are used for myiasis treatment in the villages, though the scientific background of these medicines are remained unknown. Insecticides and pesticides in the form of ointments are considered more effective against screwworm than in the form of spraying particles, the reasons for this being that C. bezziana flies do not stay long on the body of animals except whilst laying their eggs. Some drugs including ivermectine and methoxychlor are also effective against screwworm. Key words : Myiasis, Chrysomya bezziana, screwworm, epidemiology